The use of non-verbal displays in framing COVID-19 disinformation in Europe: an exploratory account - Dumitrescu, Delia; Trpkovic, Mina (Frontiers in psychology, 2022)
While online disinformation practices have grown exponentially over the past decade, the COVID-19 pandemic provides arguably the best opportunity to date to study such communications at a cross-national level. Using the data provided by the International Fact-Checking Network (IFCN), we examine the strategic uses of non-verbal and verbal arguments to push disinformation through social media and websites during the first wave of lockdowns in 2020 across 16 European countries. Our paper extends the work by Brennen et al. (2021) on the use of visuals in COVID-19 misinformation claims by investigating the use of facial emotional expressions and body pose depictions in conjunction with framing elements such as problems identified and attribution of responsibility in the construction of disinformation messages. Our European-wide comparative analysis of 174 messages indexed by the IFCN during the months of April and May 2020 helps provide a rounder understanding of the use of non-verbal devices in advancing COVID-19 disinformation across the continent, and can provide the basis for a framework for further study of the strategic use of non-verbal devices in COVID-19 disinformation world-wide.
Gesehen am 21.06.2022